Advanced Targeted Drug Delivery of Fluoresceine Isothiocyanate by FOL-PEG-g-PEI-GAL conjugate as the Novel Nanoparticles - Ghiamkazemi, Sepideh; Amanzadeh, Amir; Dinarvand, Rasoul; Amini, Mohsen; Rafiee Tehrani, Morteza (International Pharmacy Acta, 2018)
Abstract Polyethylenimine (PEI) is a well-known cationic polymer that has gained recent attention as a transfection and transduction agent. However; it is extremely cytotoxic in many cell lines because of its high surface charge (about +40 mV), non-biodegradability and non-biocompatibility. Other drawbacks of this polymer include, low duration of expression, non-specific cell uptake and instability in blood circulation. To enhance Polyethyleneimine biocompatibility, the graft pegylated copolymer was synthesized. To target cancer liver cells, two targeting ligands folic acid and galactose (lactobionic acid) were attached with graft Pegylated copolymer to increase specifically the entrance of this new targeted copolymer to cancer liver cells, because the folic acid and lactobionic acid receptors are over expressed only on human hepatocyte carcinoma. The composition of this new conjugated copolymer was characterized using 1H-NMR spectra. Its molecular weight and zeta potential were compared to polyethyleneimine. To study the entrance of this targeted carrier to human hepatocyte carcinoma (HepG2), fluoresceine isothiocyanate (FITC) as a model drug was conjugated to this novel carrier and the emission of green fluorescent was determined from three cell lines (HEK293, KB and HepG2) and compared with fluoresceine isothiocyanate alone. Introduction: In recent years, there has been an enormous interest in the formulation of a targeted carrier for a specific population of cells, either locally or systematically. The targeted drug delivery system can be achieved by either non-polymeric or polymeric carrier methods. Novel drug delivery by non-polymeric carriers has been studied for years; however, the broad use of this system is affected by the limited size of material delivered, cytotoxicity and no targeting interaction to certain cells. Polymeric drug delivery carriers have become a promising alternative since the carriers could be synthesized with higher purity and quality degree and less immunogenic response than the viral and lipidic carriers for drug targeting. Methods and results: First of all, pegylated polyethylenimine (PEG-g-PEI) was synthesized and then folate-PEG-g-PEI, folate-PEG-g-PEI-galactose was prepared and folate-PEG-g-PEI-galactose conjugated with Fluorescein isothiocyanat as a model drug. To investigate transduction efficacy of FOL-PEG-g-PEI-GAL conjugated with FITC, as a drug model, the fluorescent activity was measured in transduced HepG2, HEK293 and KB cell lines and the results are monitored.